The Relationship Between Functional Movement Screening With Fitness Factors in Female Athlete Students - Maral Entezami; Hasan Daneshmandi; Ali Shamsi Majelan (Biyumikānīk-i varzishī, 2021)
Objective: The study examines the relationship between Functional Movement Screening (FMS) tests with fitness factors in female athlete students. Methods: The study population includes 30 female athlete students (Mean±SD of age: 23.36±3.10; height: 163.45±5.06; and 57.40±6.43). FMS test was used for measuring movement patterns. Sargent test was used to measure lower limb power, Y-test was used to measure dynamic balance, Stork test was used to measure static balance, and flexor/extensor muscle endurance tests were also used to measure trunk muscle endurance. In addition, Pearson correlation was used to evaluate the relationship between scores of functional motion screening and fitness factors. Multivariate regression was used to solve the linear regression equation. The data analyzed in SPSS software, V. 22 at significance level of P≥0.05. Results: Our results showed no significant relationship between FMS test with fitness factors (P>0.05). Conclusion: There is no significant relationship between total score of FMS test with fitness factors. It seems that FMS addresses the quality of basic motor activities while fitness factors determine sport skills; thus, FMS scores can’t explain fitness factors.